Political Movement By Apolitical Activist: Gezi Park Protests - Polat, Ferihan; Subay, Ozlem Ozdesim (European Scientific Journal, ESJ, 2016)
Gezi Park Protests leaving its mark in the June of 2015, is understood from so many perspectives by national and international academicians. On the one hand, some social scientists recognize this movement as apolitical action by analyzing the identity of activist, on the other hand, some of them claims that this movement is a political one by pointing out that the aim of the movement is against the Ak Party Government especially ErdoÄŸan himself. This study aiming to understand Gezi Park Protests puts forward that having apolitical identity of activists is not enough to recognize the movement as apolitical one and also claiming that having political action cannot be explained by the idea that the movement is just against the Ak Party Government. This study justifying that this movement cannot be explained by the idea of domestic political conflict and separation as Turkey is a part of global capitalist order, focuses on dimensions of crossing national borders. Beyond the evaluation of Gezi Park Protests as an international conspiracy, interpretation of this movement as a part of the growing public protests against the system on a global scale is a more plausible perspective to understand the multidimensional social reality.